Once more about the necessity of the system of scientific support of tourism development in Kazakhstan (Journal of Geography and Environmental Management, 2018)
The article discusses the causes of inadequate development of tourismin Kazakhstan and the need for the country’s system of scientific supportfor its development and territorial organization. The three main objectivesof the establishing modern high-performance tourism industry are analyzed.In particular, the necessaryrestructuring of tourism management atthe state level and the real support of tourism as a promising sector fromthe State. The second important task is the development of the tourism scienceand scientific support for the implementation of the System tourismdevelopment plans in Kazakhstan, including the territorialorganizationand infrastructure development. And the third – personnel training, includingscientific and pedagogical, capable of ensuring the competitiveness ofKazakhstan’s tourism on the international market.